Leaf Morphology Traits of Shorea spp in Ex-Situ KHDTK Haurbentes - Rosdayanti, Henti; Siregar, Ulfah Juniarti; Siregar, Iskandar Z. (Media Konservasi, 2019)
Shorea is a genus of the Dipterocarpaceae family which shows high economic and ecological values. Currently, market demand for wood is still met from natural forests that are degrading due to over exploitation. The degraded forests are included in the rehabilitation program that require significant number of planting stocks, mainly from seedlings or wildlings. Correct species identification of planting stocks, particularly wildlings, is an important first step in planting activities and it is relevant with Shorea spp planting stocks due to leaf morphology traits. This study was aimed to examine the traits of leaf morphology of four Shorea species for easy field identification. Samples were taken from five trees for each species. Morphological trait identification was conducted by leaf observation and measurement. The results showed that all four species had the same apex shape. Six of the twelve morphological characteristic of the variable character can influence the morphological characteristics of the leaves, namely the roving leaf, leaf area, leaf length, aspect ratio, form factorand perimeter ratio of diameter. S. leprosula is similar to S. parvifolia, while S. ovalis is similar to S. guiso. Shorea leaf character S. parvifolia differentiated from S. leprosula, while Shorea ovalis similar to Shorea guiso. The LP variable (length from the base of the leaf to the widest point of the leaf) is a variable that can be used as aleaf morphological characteristic of the four Shorea which are compared because each one has a different value. S. ovalis has the highest LP value, followed by S. guiso and S. leprosula, while S. parvifolia has the lowest LP value. Keywords: apex shape, identification, leaf morphology traits, Shorea